Navigating the paradox between professional challenges and teacher well-being: The role of strategies within the resilience process - Krummenacher, Isabelle; Hascher, Tina; Mansfield, Caroline; Beltman, Susan; Mori, Julia; Guidon, Irene (Frontline Learning Research, 2024)
Teaching is an immensely complex profession that often requires managing multiple and varied professional challenges. Despite these challenges, teachers tend to report moderate to high levels of well-being. This qualitative study explored this paradox by investigating the professional challenges reported and the coping strategies Swiss teachers use to support their well-being. Relational problem-solving was identified as a commonly used strategy when professional challenges occur. The unique contribution of this study lies in its further elucidation of the complex relationship between teachers’ professional challenges and well-being embedded in a resilience process. The results of this study provide implications for understanding how to support teachers’ resilience and to design interventions to enhance teachers’ well-being.